Cancer-associated fibroblasts promote hepatocellular carcinoma progression through downregulation of exosomal miR-150-3p. Issue 2 (February 2021) - Yugawa, Kyohei; Yoshizumi, Tomoharu; Mano, Yohei; Itoh, Shinji; Harada, Noboru; Ikegami, Toru; Kohashi, Kenichi; Oda, Yoshinao; Mori, Masaki
Abstract: Purpose: Hepatocellular carcinoma (HCC) is a common and deadly cancer. The prognosis of HCC is poor and is related to tumor progression. The malignant potential of HCC is regulated by the tumor microenvironment (TME). As cancer-associated fibroblasts (CAFs) help regulate tumor progression, understanding how they function in HCC could improve patient outcomes. The aim of this study was to determine whether specific microRNAs (miRNAs) in exosomes derived from CAFs might be involved in HCC progression. Methods: MiRNA microarray assay was used to analyze miRNA profiles of exosomes derived from CAFs and normal fibroblasts (NFs) in HCC. Migration and invasion assays were performed to examine the effects of miR-150-3p on HCC in vitro . In addition, the relationships between prognosis of HCC patients and miR-150-3p expression in HCC tissues and plasma exosomes were retrospectively analyzed. Results: MiR-150-3p was significantly reduced in CAFs-derived exosomes, and inhibited HCC migration and invasiveness. MiR-150-3p was transferred from CAFs transfected miR-150-3p to HCC cells through exosomes, and abrogated HCC migration and invasiveness. Furthermore, low miR-150-3p expression in HCC tissues was a significant risk factor for recurrence in HCC patients. More importantly, survival rate in patients with low miR-150-3p levels in plasma exosomes was significantly poor compared with that in patients with high miR-150-3p levels. Conclusions: Overall, our findings suggest that the loss of antitumoral miR-150-3p in CAFs-derived exosomes greatly promotes HCC progression. Exosomal miR-150-3p is a potential prognostic biomarker, and transferring miR-150-3p-loaded exosomes to HCC cells might become a novel therapeutic option. Highlights: MiR-150-3p is reduced in the exosomes of CAFs derived from HCC specimens. Evaluation of exosomal miR-150-3p could help stratify risk in patients with HCC. Transfer of exosomal miR-150-3p to HCC cells may have therapeutic applications.